Konsep Akad Salam pada Jual Beli Pre Order Online Shop dalam Perspektif Hukum Islam - Reza Safri Nasrullah, Muhammad; Zaibi Amalia, Nur; Mu’is, Ahmad (Tasyri' : Journal of Islamic Law, 2025)
This research aims to examine the suitability of the concept of salam contract in Islamic law with the pre-order buying and selling system in online shops, and analyze its implementation in creating fair and Sharia-compliant transactions. The salam contract, as a form of contract in muamalah fiqh, allows for advance payment for goods that will be delivered at a later date. This characteristic has relevance to the pre-order system that is widely used in digital transactions today. This research uses the library research method. Data were collected through a literature study of primary and secondary sources, such as fiqh books, scientific journals, and relevant papers. The analysis is conducted to identify the similarities in principle between salam and pre-order contracts, and evaluate the potential problems that may arise in their application. The results show that the salam contract can be used as a reference in the pre-order system, as long as it fulfills the sharia requirements, such as full payment in advance, clarity of goods specifications, and certainty of delivery time. The application of the salam contract principle to pre-order sales in online shops not only strengthens the sharia legal aspects, but also increases the trust between sellers and buyers. This research confirms that the salam contract is a flexible and relevant solution in modern sharia-based economic transactions.